PENGARUH ALAT PERAGA RODA SIKLUS TERHADAP PEMAHAMAN KONSEP IPAS PADA SISWA KELAS III SEKOLAH DASAR - Refni Yunita; Neni Hermita; Jesi Alexander Alim (Tunjuk Ajar : Jurnal Penelitian Ilmu Pendidikan, 2026)
This study aims to examine the effect of using a life cycle wheel instructional aid on Grade III students’ understanding of IPAS concepts at SDN 192 Pekanbaru. The study employed an experimental approach using a one-group pretest–posttest design involving 34 students. The intervention was implemented through IPAS instruction utilizing the life cycle wheel instructional aid over four instructional sessions. Research instruments included a 25-item multiple-choice test and observation sheets to assess students’ attitudes and skills. The findings indicate that the mean pre-test score of 62.24 increased to 83.65 on the post-test. The Wilcoxon signed-rank test revealed a statistically significant difference between pre-test and post-test scores, while the N-gain analysis yielded a value of 0.5882 (58.82%), which falls within the moderate improvement category and indicates a fairly effective level of effectiveness. In addition to improvements in learning outcomes, observational data demonstrated positive developments in students’ attitudes and skills throughout the learning process. Therefore, the use of the life cycle wheel instructional aid has a statistically significant and fairly effective impact on enhancing Grade III elementary school students’ understanding of IPAS concepts.